Prediction of athletic performance through nutrition knowledge and practice: A cross-sectional study among young team athletes - Debnath, M.; Chatterjee, S.; Bandyopadhyay, A.; Datta, G.; Kumar Dey, S. (SportMont, 2019)
Optimal fuelling is an essential requisite for athletes to excel to their best ability (Maughan & Burke, 2011; Kerksick et al., 2008). Apart from nutrition playing an influential role in enhancing on-field performance; it also promotes muscle growth, prevents injury, accelerates recovery, and supports rehabilitation (Mahan & Stump, 1998). Undoubtedly, athletes` daily diet and fluid intake affect their health, body composition, and substrate availability during exercise as well as recovery time (American Dietetic Association, 2009). Adequate nutrition, which can be reached through sufficient nutrition knowledge (NK), is an integral part of a training programme